EFFECTIVE MANAGEMENT OF SCHOOL PLANT FACILITIES IN PRIMARY SCHOOLS IN NIGERIA - I., Medinat Rabi’u (Sokoto Educational Review, 2020)
In the education sector today, there is no doubt that there is general outcry that standards are falling. The parents blamed the teachers and the children for lack of seriousness as well as the governments for unattractive condition of service, also for provision of poor physical facilities in the classrooms, furniture meant for thirty pupils are used by double the number. School building meant to accommodate hundred pupils now accommodates triple the number and some outdated equipment used in the 1950s are still being used to impact knowledge to school children. Other problems identified are peculiar to ineffective management of education in primary schools in Nigeria. It is for this reason that this paper wish to discuss the need for school plants and instructional facilities in schools, discuss the definition of terms, and the effective management of the instructional facilities in schools. The paper further points out the need for the use of these, facilities for the successful teaching and learning in the classroom followed by the suggestions and conclusion.